BUYING BEHAVIOR IN ONLINE FOOD DELIVERY APPLICATIONS DURING THE COVID-19 PANDEMIC - Niken Permata Sari; Bahri; Ardhi (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2022)
This study aims to review the effect of discount framing, brand reputation, purchase intention, and actual behavior based on online food delivery applications during the COVID-19 pandemic. The population, in this study are users of online food delivery applications throughout Indonesia, with the unit of analysis being the individual. Sampling in this study used the purposive method, namely respondents who filled out online questionnaires with total of 119. The data analysis technique in this study used SEM-AMOS version 23. The results showed that discount framing had a positive effect on brand reputation and purchase intention, brand reputation has a positive effect on purchase intention, and purchase intention has a positive effect on actual behavior. The implications of the results of this study for application owners are to know the effect of discount framing, brand reputation, and purchase intention so that they can take strategies and policies related to these matters. For application, users are to be able to use applications that provide discount framing according to their needs.